1984
DOI: 10.1063/1.447848
|View full text |Cite
|
Sign up to set email alerts
|

Total and partial electron collisional ionization cross sections for CH4, C2H6, SiH4, and Si2H6

Abstract: The total and partial electron collisional ionization cross sections for CH4, C2H6, SiH4, and Si2H6 have been measured for electron energies from threshold to 300 eV. Comparisons are made to earlier measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
119
6
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(146 citation statements)
references
References 14 publications
20
119
6
1
Order By: Relevance
“…For methane, the additivity rule uses 12 constants for curve A and 24 constants for curve B. The experimental data by Chatham et al 39 ͑not shown in the figure͒ are very close to those by Durić et al…”
Section: Hydrocarbonssupporting
confidence: 74%
“…For methane, the additivity rule uses 12 constants for curve A and 24 constants for curve B. The experimental data by Chatham et al 39 ͑not shown in the figure͒ are very close to those by Durić et al…”
Section: Hydrocarbonssupporting
confidence: 74%
“…4͒ that this is not the case for SiH 4 , whose vertical IP is 12.7 eV, 20 while the adiabatic IP is 11.65 eV. One feature that distinguishes SiH 4 from CH 4 and NH 3 is that few parent ions, SiH 4 ϩ , are generated in the former, 15,17 while the parent ions of the latter are not difficult to produce.…”
Section: Discussionmentioning
confidence: 87%
“…For Si 2 H 6 , the experimental results of Chatham et al 17 and Krishnakumar and Srivastava 18 differ markedly in the peak region ͑Fig. 5͒.…”
Section: B Silane (Sih 4 ) and Disilane (Si 2 H 6 )mentioning
confidence: 91%
See 1 more Smart Citation
“…Previous results (Table 1) are several eV higher in energy. By comparing the values given in Table. l it is seen that the above value concurs with the energy of formation of process [7] but is significantly lower than other measured values except for that of Chatham et al (12) which has a large error. This discrepancy is indicative .of -the lack of sensitivity of these previous works.…”
Section: C2hmentioning
confidence: 56%